2017
DOI: 10.1371/journal.pone.0188052
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc sulfate contributes to promote telomere length extension via increasing telomerase gene expression, telomerase activity and change in the TERT gene promoter CpG island methylation status of human adipose-derived mesenchymal stem cells

Abstract: The use of mesenchymal stem cells (MSCs) for cell therapy and regenerative medicine has received widespread attention over the past few years, but their application can be complicated by factors such as reduction in proliferation potential, the senescent tendency of the MSCs upon expansion and their age-dependent decline in number and function. It was shown that all the mentioned features were accompanied by a reduction in telomerase activity and telomere shortening. Furthermore, the role of epigenetic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…Culture of hMSCs at lower concentrations (3–5%) of [O 2 ] revealed a significant increase in culture lifespan and better cellular quality, which was associated with a favorable metabolic state of increased glycolysis and decreased oxidative phosphorylation, resulting in reduced levels of oxidative stress [ 3 8 ]. In agreement with these observations are the results of several studies using ex vivo treatments with antioxidants (reviewed in [ 9 ]); for example, short-term treatment of hADSCs with physiological concentrations of zinc sulphate promotes telomere length extension. It is important to note while low [O 2 ] is usually referred to as hypoxia, low O 2 tensions are considered normoxic in several organs [ 10 , 11 ].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Culture of hMSCs at lower concentrations (3–5%) of [O 2 ] revealed a significant increase in culture lifespan and better cellular quality, which was associated with a favorable metabolic state of increased glycolysis and decreased oxidative phosphorylation, resulting in reduced levels of oxidative stress [ 3 8 ]. In agreement with these observations are the results of several studies using ex vivo treatments with antioxidants (reviewed in [ 9 ]); for example, short-term treatment of hADSCs with physiological concentrations of zinc sulphate promotes telomere length extension. It is important to note while low [O 2 ] is usually referred to as hypoxia, low O 2 tensions are considered normoxic in several organs [ 10 , 11 ].…”
Section: Introductionsupporting
confidence: 70%
“…The main pathways activated in senescent cells are Rb/p16 and p53/21, leading to progressive cell cycle blockade and cell growth arrest. In line with this, the positive effects on hADSCs by short-term treatment with zinc sulphate are mediated by modulation of the methylation status of the promoter of TERT, the telomerase catalytic subunit [ 9 ]. Many studies consider senescence as a tumor suppressor network mechanism (reviewed in [ 15 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Farahzadi R et al . reported that Zinc sulfate promoted telomere length extension via increasing telomerase gene expression 28 . Furthermore, the dietary antioxidants supported the maintenance of telomere length, particularly vitamin and soybean phospholipid 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Samples were obtained after signed informed consent was provided by the donors or their legal representatives, in accordance with guidelines for research involving human subjects and with the approval of the Ethics Committee of Fundação Oswaldo Cruz, Brazil (approval number 419/07). hASCs were isolated and expanded as previously described elsewhere 51 with modifications. Briefly, 200 ml of adipose tissue were digested with 1 mg/ml collagenase type I (GIBCO) solution for 30 min at 37 °C, 5% CO 2 under constant shaking.…”
Section: Methodsmentioning
confidence: 99%